Pluralisme Agama sebuah Keniscayaan - Taslim HM. Yasin (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2013)
Ahlu al-Kitab has become one of the unique concepts in Islam. Islam  acknow-ledges the holy books and the ummah prior to Islam. This  acknowledgement does not means that all religions are the similar to all aspects.  Since each religion has its distinct creeds, rituals and code of conducts, all  religions are to respect and tolerate each other. Through respect and tolerance, all  religions can cooperate and solve problems of religious, social, political and  cultural issues emerging in their ummah. This is what calls religious pluralism concept that aims to built a harmonious and peaceful community, the community  with pluralistic beliefs, but united to handle the problems of its people.